Representasi Feminisme dalam Lirik Lagu “Anganku Anganmu” Karya Raisa Feat Isyana Sarasvati - Putri Yusma Dewi Siagian (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2024)
The purpose of this research is to study the meaning of feminism contained in the lyrics of Raisa and Isyana Sarasvati's song "AngankuAnganmu" using Roland Barthes's semiotic approach. This song not only shows the principles of solidarity, freedom, and gender equality, but also fights many myths that prevent women from becoming better. This study found that the lyrics of the song contain a message that encourages women to voice their opinions, overcome conflicts, and pursue their dreams without being hindered by social norms. This discovery was made using a qualitative descriptive research method. This study shows that the art of music can be an effective tool to convey messages about feminism and support the struggle for gender equality through the representation of signs and meanings contained in lyrics.